FAKTOR - FAKTOR YANG MEMENGARUHI OPINI AUDIT ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA - Rumanti, Helda; Sari, Kartika Rachma; Astuti, Indriani Indah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
Local Government Financial Reports (LKPD) represent a form of transparency and accountability in regional financial management, evaluated through audit opinions issued by the Supreme Audit Agency (BPK). However, over the past three years, the quality of audit opinions on LKPD in Indonesia has declined, prompting the need to analyze the factors influencing this trend. This study aims to investigate the effects of audit findings, follow-up on audit recommendations, local government size, resolution of regional losses, and timeliness of financial report submission on LKPD audit opinions. Employing a quantitative research design, this study utilizes secondary data from the financial reports of 495 local governments in Indonesia spanning 2021 to 2023. Data analysis was conducted using logistic regression with SPSS version 26. The results indicate that audit findings negatively affect LKPD audit opinions, while timely submission of financial reports and follow-up on audit recommendations have a positive impact. Meanwhile, local government size and resolution of regional losses do not show a significant influence on LKPD audit opinions in Indonesia.